2013
DOI: 10.1152/japplphysiol.01460.2012
|View full text |Cite
|
Sign up to set email alerts
|

Increased mechanical strain imposed on murine lungs during ventilation in vivo depresses airway responsiveness and activation of protein kinase Akt

Abstract: Continuous positive airway pressure (CPAP) administered to tracheostomized rabbits and ferrets for 4 days or 2 wk suppresses bronchial reactivity in vivo and suppresses airway reactivity in lobes and tracheal segments isolated from these animals. In vitro studies of canine tracheal smooth muscle tissues indicate that mechanical loading suppresses the activation of the growth regulatory kinase, Akt, and that Akt is a negative regulator of smooth muscle differentiation. The transduction of mechanical signals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Few neonatal animal studies have investigated the effects of CPAP on neonatal AW reactivity and its effects on adults are conflicting ( 17 21 , 28 ). The discrepancies between these studies suggest the effects of CPAP are multifactorial and could depend on numerous factors including the duration, intensity and experimental setting in which positive pressure was delivered to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Few neonatal animal studies have investigated the effects of CPAP on neonatal AW reactivity and its effects on adults are conflicting ( 17 21 , 28 ). The discrepancies between these studies suggest the effects of CPAP are multifactorial and could depend on numerous factors including the duration, intensity and experimental setting in which positive pressure was delivered to the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports in lung tissue and smooth muscle cells have found that an increase in pressure on the order of 1 mmHg decreases focal adhesion activation of the protein kinase, Akt. 42, 43 Focal adhesions that anchor the osteoblasts to the extracellular matrix play a key role in translating these mechanical forces to the intracellular cytoskeleton framework and into a biochemical response. The interaction between focal adhesions and the extracellular matrix can change under different mechanical loads due to conformational changes to the integrin structure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects of CPAP persisted for at least 24 h (61). In a recent study by Xue and colleagues (63), CPAP for only 2 h was sufficient to alter airway responsiveness in mice.…”
Section: Duration Of Length Adaptationmentioning
confidence: 93%
“…Several previous studies examining the effect of chronic exposure to increased P tm on airway function all show that chronic inflation suppresses airway narrowing (52,(61)(62)(63). Indeed, continuous positive airway pressure (CPAP) has been suggested as a novel treatment for asthma (43).…”
Section: Duration Of Length Adaptationmentioning
confidence: 99%